The Lon Protease Is Essential for Full Virulence in Pseudomonas aeruginosa - Breidenstein, Elena B. M.; Janot, Laure; Strehmel, Janine; Fernandez, Lucia; Taylor, Patrick K.; Kukavica-Ibrulj, Irena; Gellatly, Shaan L.; Levesque, Roger C.; Overhage, Joerg; Hancock, Robert E. W. (PLOS ONE, 2012)
Pseudomonas aeruginosa PAO1 lon mutants are supersusceptible to ciprofloxacin, and exhibit a defect in cell division and in virulence-related properties, such as swarming, twitching and biofilm formation, despite the fact that the Lon protease is not a traditional regulator. Here we set out to investigate the influence of a lon mutation in a series of infection models. It was demonstrated that the lon mutant had a defect in cytotoxicity towards epithelial cells, was less virulent in an amoeba model as well as a mouse acute lung infection model, and impacted on in vivo survival in a rat model of chronic infection. Using qRT-PCR it was demonstrated that the lon mutation led to a down-regulation of Type III secretion genes. The Lon protease also influenced motility and biofilm formation in a mucin-rich environment. Thus alterations in several virulence-related processes in vitro in a lon mutant were reflected by defective virulence in vivo.